INFLUENCE OF MOLECULAR-GENETIC FACTORS ON IMMUNE INDICATORS IN MEN WITH IMPAIRED FERTILITY (Archive of Conferences, 2020)
Genetic factors account for 30-50% of all cases of severe forms of male infertility. Spermatogenesis is a complex biological process that depends on a precisely controlled cascade of activation and deactivation of certain genes. The result of these genes work is the process of maturation of spermatozoa from progenitor cells (spermatogones). Among gene factors, associated with azoospermia, CFTR gene mutations / variants are the most common. They can cause cystic fibrosis (CF) and congenital bilateral aplasia of vas deferens (CBAVD) syndrome, leading to bilateral aplasia and obstruction of the vas deferens. CF is one of the most common monogenic diseases with an autosomal recessive mode of inheritance. More than 95% of men with CF and all patients with CBAVD have infertility due to obstructive azoospermia. In 88% of men with CF, bilateral obstruction of the vas deferens at the level of the epididymis and / or vas deferens and aplasia of the seminal vesicles are noted. Obstructive azoospermia, observed in men in 25% of cases, is a consequence of unilateral or bilateral congenital absence of the vas deferens, which arose due to mutations in CFTR gene.